Effect of Sn nanoparticles on the optical properties of PEDOT:PSS thin films - Aly, Kamal A.; Ismail, Yasser A. M.; Salman S. Alsulami, Ziad; Abolibda, Tariq Z.; Almohammedi, Abdullah; Gomha, Sobhi M.; Ahmed, Hoda A.; Ibrahim, Mohamed S. (Frontiers in Physics, 2024)
In the present work, the authors try to improve the optical properties of PEDOT:PSS films through the incorporation of pure Sn nanoparticles (NPs) prepared using the ultrasonic ablation technique. The index of refraction (n) and extinction coefficient (k) for PEDOT:PSS films with different concentrations of Sn are precisely estimated using the measured film transmission and reflection spectra. The obtained results of n are well explained in terms of Sellmeier's dispersal model. The dispersive factors have been estimated and well interpreted. The E_g values of PEDOT:PSS films were found to improve, whereas the n values decreased with increasing Sn contents, making these films more appropriate for organic solar cell applications. With the help of n and k values, it is easy to complete the estimation of the optical and dielectric parameters, viz., the complex dielectric constant, complex optical conductance, and nonlinear optical constants. The dielectric constant of PEDOT:PSS/Sn films is reduced with the rise of Sn contents, which directly improves the transmittance velocity and the microelectronic device efficacy and promotes the development of large-frequency and large-velocity stretchy circuit boards. The larger non-linear optical constants make the present films suitable for all optical switching, limiting, phase modulation, and frequency conversion.